The role of psychosocial resources for long-term breast, colorectal, and prostate cancer survivors: prevalence and associations with health-related quality of life - Doege, Daniela; Brenner, Hermann; Arndt, Volker (Supportive care in cancer, 2019)
Purpose: Many long-term cancer survivors still have to adjust to possible adverse consequences of the illness or treatment. Resources can play an important role in this adjustment process, but research on this topic is limited, especially for very long-term survivors. This study explores, which resources are most frequently indicated by different subgroups of cancer survivors, and what role resources play for functioning and health-related quality of life (HRQL) in cancer survivors with and without recurrence. Methods: The sample of 6030 breast, colorectal, and prostate cancer survivors (5-16 years post-diagnosis) was recruited in a German multi-regional population-based study. Personal resources were assessed by a 27-item checklist; HRQL was assessed by the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30). General linear models were used to analyze associations of resources with HRQL. Results: Participants indicated on average 11.4 (SD 5.1) resources as helpful. Family, activities with others, and partnership were indicated most commonly overall, but frequencies varied according to age, sex, and tumor site. Physical activity, health, professional help, calmness, hope, optimism, and hobbies were most important in explaining HRQL variance. Cancer survivors with recurrence and many resources were found to report similar HRQL as survivors without recurrence and only few resources. Conclusions: The study underlines the importance and situational variability of personal and social resources for cancer survivors’ HRQL, even years post-diagnosis. Not only the availability, but also the individual perception and significance of resources should be considered in follow-up cancer care.
Gesehen am 13.02.2019
Published online: 27 June 2018